(NsOCIALXNO(B-(NFILOSOFSKIE PROBLEMY \KOLOGII (B/s - (NkISELEW(B, (NnIKOLAJ nIKOLAEWI^s; (NkRISA^ENKO(B, (NwALENTIN sEMENOWI^s; (NsTOGNIJ(B, (NiWAN pETROWI^s; (NoGORODNIK(B, (Ni(B.(Nw(B.s ((NkIEW (B:s (NwY]A [KOLA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 256-270 (391 (NNAZW(B.)s
Keywords: (N|KOLOGIQ (B- (NfILOSOFSKIE PROBLEMYs